Effective Length Design of Humanoid Robot Fingers Using Biomimetic Optimization. (29th October 2015) - Kim, Byoung-Ho
In this study, we propose an effective design method for the phalangeal parameters and the total size of humanoid robot fingers based on a biomimetic optimization. For the optimization, an interphalangeal joint coordination parameter and the length constraints inherent in human fingers are considered from a biomimetic perspective. A reasonable grasp formulation is also taken into account from the viewpoint of power grasping, where the grasp space of a humanoid robot finger is importantly considered to determine the phalangeal length parameters. The usefulness of the devised biomimetic optimization method is shown through the design examples of various humanoid robot fingers. In fact, the optimization-based finger design method enables us to determine effectively the proper phalangeal size of humanoid robot fingers for human-like object handling tasks. In addition, we discuss its contribution to the structural configuration and coordinated motion of a humanoid robot finger, and address its practical availability in terms of effective finger design.